The Life of Lichen: ENY2015/IN1296, 11/2020 - Stevenson, James; Milligan, Lara B.; Gillett-Kaufman, Jennifer L. (EDIS, 2020)
Lichen represent a fascinating combination of organisms working together to form some familiar and unfamiliar growths on a variety of substrates. This fact sheet hopes to define and explain these organisms.